Effects of an 8-week whole-body electromyostimulation training on cycling performance, back pain, and posture of a 17-year-Old road cyclist - Berger, J.; Ludwig, O.; Becker, S.; Kemmler, W.; Fröhlich, M. (International Journal of Athletic Therapy & Training, 2021)
A 17-year-old male road cyclist with unspecific back pain and postural deficiency regarding the depth of the lumbar lordosis (flèche lombaire [fl]) and the upper body tilt (forward trunk tilt [tt]) absolved an 8-week whole-body electromyostimulation (WB-EMS) training to improve performance parameters and health issues. During WB-EMS, muscle groups all over the body are stimulated via external electrodes, thus creating an intensive training stimulus due to the electrically induced involuntary muscle contraction. The athlete`s posture (fl 2.2%, tt 64.3%) and back pain (54%) improved, and trunk strength increased (extension 15.5%, flexion 29.2%). This is the first WB-EMS study of a minor cyclist, suggesting positive effects of WB-EMS as a time-saving strength training method on health and strength parameters.